PROTECTIVE INFLUENCE OF FISETIN ON COGNITIVE AND BIOCHEMICAL INDICES IN N-NITROSODIETYHLAMINE TREATED DROSOPHILA MELANOGASTER - SOFIA, JENEFER; SUBRAMANIAN, PERUMAL (International Journal of Current Pharmaceutical Research, 2021)
Objective: The current investigation is intended to investigate the protecting influence of fisetin on cognitive, as well as biochemical indices in N-Nitrosodiethylamine (NDEA, a potent carcinogen), treated Drosophila melanogaster. Methods: D. melanogaster is used as a model organism for this investigation. Experimental flies are divided into four groups. Group 1–control, group 2-flies were treated with 0.01% NDEA in food medium, group 3–flies treated with 0.01% NDEA and 0.01% fisetin and group 4-flies were treated with 0.01% fisetin alone. Behavioural abnormalities (negative geotaxis, phototaxis, smell and taste chemotaxis, hygrotaxis and thermotaxis) were quantitatively observed to be deviated in NDEA treated flies compared to control but were tend to be normalized in fisetin treated flies. Results: The contents of protein carbonyl, thiobarbituric acid reactive substance (TBARS), protein thiol and lipid peroxides were noticeably augmented in NDEA treated flies than control flies and correspondingly tend to normalize in fisetin treated groups. Further, superoxide dismutase (SOD), catalase (CAT), glutathione-S-transferase (GST), glutathione peroxidise (GPX) and reduced glutathione (GSH) were decreased in NDEA treated group and were significantly increased (p<0.05) in fisetin treated groups. Conclusion: Fisetin, a bioactive phytochemical could act as a potent antioxidant and as well exhibit antiproliferative characteristics. Our investigation indicates that this could prevent the abnormalities in behaviour and redox homeostasis during carcinogenesis in D. melanogaster.